Recent Advances in Carboxylation of Furoic Acid into 2, 5‐Furandicarboxylic Acid: Pathways towards Bio‐Based Polymers. Issue 19 (17th August 2020) - Drault, Fabien; Snoussi, Youssef; Paul, Sébastien; Itabaiana, Ivaldo; Wojcieszak, Robert
Abstract: 2, 5‐furandicarboxylic acid (FDCA) is one of the most important bio‐sourced building blocks and several routes have been reported for its synthesis. FDCA is presumed to be an ideal green alternative to terephthalate, which is one of the predominant monomers in polymer industry. This Minireview concerns the synthesis of FDCA by using various carboxylation reactions and discusses the synthesis of FDCA starting from furoic acid and CO2 and using different catalytic and stoichiometric processes. This process is of high interest, as it avoids the glucose isomerization step and selectivity issues observed during the 5‐hydroxymethylfurfural oxidation step of the current alternative route to FDCA. Discussion focuses on the main parameters that govern selectivity and activity in the carboxylation processes. Moreover, various previously described processes, such as the Henkel reaction and enzymatic, homogeneous catalytic, and photoelectrocatalytic processes, are also discussed. Abstract : Getting greener with polymers : The production of new sustainable polymers is of high importance. As discussed in this Review, several methods and catalytic pathways are accessible to produce 2, 5‐furandicarboxylic acid (FDCA) from furoic acid. However, this topic still lacks systematic studies. In this review various routes to FDCA by using noncatalytic and catalytic carboxylation processes are critically discussed.